Clinical care of children and adolescents with COVID‐19: recommendations from the National COVID‐19 Clinical Evidence Taskforce. Issue 5 (24th October 2021) - Fraile Navarro, David; Tendal, Britta; Tingay, David; Vasilunas, Nan; Anderson, Lorraine; Best, James; Burns, Penelope; Cheyne, Saskia; Craig, Simon S; Erickson, Simon J; Fancourt, Nicholas SS; Goff, Zoy; et al.
Abstract: Introduction: The epidemiology and clinical manifestations of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection are different in children and adolescents compared with adults. Although coronavirus disease 2019 (COVID‐19) appears to be less common in children, with milder disease overall, severe complications may occur, including paediatric inflammatory multisystem syndrome (PIMS‐TS). Recognising the distinct needs of this population, the National COVID‐19 Clinical Evidence Taskforce formed a Paediatric and Adolescent Care Panel to provide living guidelines for Australian clinicians to manage children and adolescents with COVID‐19 and COVID‐19 complications. Living guidelines mean that these evidence‐based recommendations are updated in near real time to give reliable, contemporaneous advice to Australian clinicians providing paediatric care. Main recommendations: To date, the Taskforce has made 20 specific recommendations for children and adolescents, including definitions of disease severity, recommendations for therapy, respiratory support, and venous thromboembolism prophylaxis for COVID‐19 and for the management of PIMS‐TS. Changes in management as a result of the guidelines: The Taskforce currently recommends corticosteroids as first line treatment for acute COVID‐19 in children and adolescents who require oxygen. Tocilizumab could be considered, and remdesivir should not be administered routinely in this population. Non‐invasive ventilation or high flow nasal cannulae should be considered in children and adolescents with hypoxaemia or respiratory distress unresponsive to low flow oxygen if appropriate infection control measures can be used. Children and adolescents with PIMS‐TS should be managed by a multidisciplinary team. Intravenous immunoglobulin and corticosteroids, with concomitant aspirin and thromboprophylaxis, should be considered for the treatment of PIMS‐TS. The latest updates and full recommendations are available at www.covid19evidence.net.au .